(3GdJYQjaGJs - (3Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj,J (B816 (3g` s ((3YfJGH s)
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hGdUdGI Ydi NjQ Ndbg hHYO agPg JYQjaGJ LeYJgG hEUWdGMGJ CNPJgG ef cJH Gdbhe hQJHJgG Ydi MQha GdgLGA s
(3BNQgG (B:s
(3jhe GdLeY (B: (3hbJ GddbGA hGdhUhd GdjhfSjI (B: (3hgh jhfS Hf YHO GdQMef bGd (B: (3Gddg JYGdi Ydi GdYQT JMedg GdedGFcI hgh Cbhi efgG Je GdcJGH HYhf Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Hg eWGdH ddcJGHs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs